HIGHER GEOGRAPHIC EDUCATION IN UKRAINE (THE CURRENT STATE AND ADVANCED CARTOGRAPHIC RESEARCH) - Молочко, М. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article presents the assessment of the present state of higher geographic education in Ukraine related to the reforms which are being implemented in a complex socio-political situation. A number of fundamental disciplines of a geographic profile have disappeared from the list of specialties and skills required for higher education seekers. Their withdrawal resembles an undeclared war in the scientific field, when reasoned objections are ignored. Countering negative processes in higher education is seen in support of the whole extensive system of geographical sciences, including war- or even military geography, by the self-governing Taras Shevchenko National University of Kyiv. Changes to higher geographic education, in particular in its cartographic field, and some of the outcomes of pre-cartographic research are also considered in the article. Keywords: higher geographic education, branch of knowledge, speciality, educational program, cartographic modeling.